Value-Added Global Database Search through Wide Area Network - Baokar, Anjali; Sundareshwa, P.R.; Joshi, M.R. (DESIDOC Journal of Library & Information Technology, 2002)
Abstract : Online database searches have become common and a number of American and European databases, notably those related to science and engineering have become very popular due to their specialisation in specific fields. Although telecommunication charges are relatively low, specific database charges are substantiHI, depending upon the area of specialisation. This paper discusses the access and search of global databases, value addition through organisation of the received data and sharing of the organised data in the local area network. The original organised database when accessed and downloaded becomes an ASCII file. If the selected database is to be reconstructed at the receiving end, it i s a laborious task of manual data entry which could be very slow and error-prone. A program developed for automated conversion of the ASCII file into a standard database format is described. http://dx.doi.org/10.14429/dbit.13.3.3077